Comparison of drug-induced hepato-toxicity in female patients during anti-retroviral therapy - Nhiwatiwa, Melody (My University, 2014)
Long term antiretroviral therapy (ART) use is known to cause various toxic adverse effects in patients. Hepato-toxicity is one of the most significant adverse effects which have been associated with all antiretroviral therapy drugs in South Africa and worldwide.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Medicine in Pharmacotherapy, Johannesburg, 2011
Keywords: Antiretroviral Therapy, Highly Active; Drug-Induced Liver Injury; Liver--drug effects